Kirčiuotų ilgųjų balsių trukmė lietuvių bendrinės kalbos frazėse - Anusienė, Lilija (Kalbotyra, 1983)
The purpose of this research was to study the differences of duration between vowels with falling and rising accent in present-day Lithuanian utterances. The results obtained revealed that there is almost no difference of duration in the vowels with falling and rising accent. It leads to the conclusion that duration is not the main factor in the differentiation of accent type. Further research of the duration of long stressed vowels, irrespective of the type of accent, revealed that the results obtained correspond to the rule nearly general in all languages: the more close (higher) a vowel is, the shorter is its duration. The characteristic feature of mid-open vowels [ė-] and [o-] is that they greatly differ in duration from open vowels [e-] and [a-], but almost do not differ from close vowels [i-] and [u-]. Front vowels [ė-] and [i-] are shorter than back vowels [o-] and [u-].